2000
DOI: 10.5860/crl.61.5.410
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Authorship in the Journal Literature: Perspectives for Academic Librarians Who Wish to Publish

Abstract: Academic librarians, particularly college librarians, may increase their contributions to the professional literature through collaborative authorship. For example, university librarians, who published 69 percent of the articles in College & Research Libraries and the Journal of Academic Librarianship between 1986 and 1996, contributed almost 90 percent of the coauthored research in those core journals. This study examines the increase in collaboration in the literature of academic librarianship and in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 25 publications
2
28
0
1
Order By: Relevance
“…6 Besides Budd's discipline-wide study, at least nine articles since 1999 have studied publication in LIS on a smaller scale, such as one or two journals, an individual institution, or a single state. 7 Results reported in these articles provide a context for the findings of the present study. The present article discusses the relevant parts of these articles and older studies in relation to the results of the present investigation.…”
Section: May 2006mentioning
confidence: 92%
“…6 Besides Budd's discipline-wide study, at least nine articles since 1999 have studied publication in LIS on a smaller scale, such as one or two journals, an individual institution, or a single state. 7 Results reported in these articles provide a context for the findings of the present study. The present article discusses the relevant parts of these articles and older studies in relation to the results of the present investigation.…”
Section: May 2006mentioning
confidence: 92%
“…In social sciences, such as library science, collaborative writing has increased dramatically over the past 25 years (Bahr & Harrison, 2000). In other disciplines, such as the sciences and education, collaborative writing is the norm.…”
Section: Introductionmentioning
confidence: 99%
“…In other disciplines, such as the sciences and education, collaborative writing is the norm. Bahr and Harrison (2000) came to the conclusion that "... as evidenced in the sciences and social sciences, collaboration encourages author productivity and enhances article quality. As research becomes more quantitative, collaboration increases" (p. 417).…”
Section: Introductionmentioning
confidence: 99%
“…The first a ributes the growth in collaboration to the increase in female authors. 25 Alice Harrison Bahr and Mickey Zemon (2000) suggested that "women are more likely to collaborate than men." 26 As the number of women presenters increased, one would expect an increase in the overall collaboration rate-as has happened.…”
Section: Collaborationmentioning
confidence: 99%
“…25 Alice Harrison Bahr and Mickey Zemon (2000) suggested that "women are more likely to collaborate than men." 26 As the number of women presenters increased, one would expect an increase in the overall collaboration rate-as has happened. However, when the collaboration rate for men and women are compared the differences are small.…”
Section: Collaborationmentioning
confidence: 99%